Impact of woody encroachment on soil organic carbon storage in the Lopé National Park, Gabon. (14th September 2016) - Chiti, Tommaso; Mihindou, Vianet; Jeffery, Kathryn J.; Malhi, Yadvinder; De Oliveira, Fabiane L.; White, Lee J. T.; Valentini, Riccardo
Abstract: This study quantifies changes in soil organic carbon (SOC) stock as a result of woody encroachment on savannas. Changes in SOC stocks occur below 30 cm depth, indicating the subsoil as the principal compartment contributing to SOC sequestration, and suggesting the need to consider the entire profile (0–100 cm) to thoroughly assess the effect of woody encroachment on SOC stocks.